AB0435 The treatment pattern of tocilizumab in patients with rheumatoid arthritis in china: a multicenter observational study. (12th June 2018) - Zhang, F.; ,; Dong, Lingli.; Li, Yasong.; Xiao, Changhong.; Shi, Xiaofei.; Zhang, Yan.; Li, Qin.; Liu, Yi.; Zhou, Bin.
Abstract : Background: Tocilizumab (TCZ) is a humanised monoclonal antibody targeting interleukin-6 receptor. Since TCZ Label for RA has been issued in many countries, administration patterns and dose modifications for managing adverse events (AEs) seems differ depending on clinical opinion. Few data are available from real world practice in China. Objectives: To observe in routine clinical practice the treatment patterns of TCZ in RA patients with regard to persistence on drug and adherence to the licensed label recommendations. Methods: This a 6 month non-interventional, multi-centre study enrolled patients with moderate to severe RA diagnosed per revised 1987 ACR criteria (age ≥18 years) and being treated with TCZ. Data was recorded during routine visit. The primary variable was the proportion of patients on TCZ treatment after 6 months. Results: Of 407 patients from 23 centres in China, 396 were eligible, including 330 (83.3%) women. The mean age was 49.1±13.44 years. The mean RA diagnosis course was 5.4±6.24 years. Among 396 patients, 250 (63.1%) were RF positive, 235 (59.3%) were anti-CCP positive and 123 (31.1%) had anaemia (Hb <90 g/L). Of eligible patients, 293 (74.0%) completed the study. The primary reason of premature termination was treatment costs (n=49, 12.4%). There were 37 (9.3%) patients received anti-TNF biologics previously and 330 (83.3%) received concomitant DMARDs, of which 84 (21.2%), 149 (37.7%) and 97 (24.5%) received single, 2 or ≥3 types of DAMRDs, respectively. Methotrexate (n=255, 64.4%) and Leflunomide (n=184, 46.5%) were the most commonly used DMARDs. A total of 126 and 197 patients received corticosteroids or nonsteroidal anti-inflammatory drugs (NSAIDs), respectively. During 6 months observation, 21.0% and 67.7% had TCZ dose modification or discontinuation, respectively. At month 3 and month 6, 161 (40.7%) and 102 (25.8%) kept TCZ treatment, respectively. The mean frequency of TCZ usage was 3.7±1.62. Effectiveness of TCZ was analysed in patients who were still using TCZ at month 6. The mean score of total TJC (28-joint count) at baseline and at month 6 was 11.2±8.0 (n=63) and 2.3±4.12 (n=77), respectively; mean change from baseline was −9.5±8.02 (n=53). The mean score of total SJC (28-joint count) at baseline and at month 6 was 8.0±6.81 (n=63) and 1.7±2.35 (n=77), respectively; mean change from baseline was −6.5±7.2 (n=53). The mean score of DAS28 at baseline and at month 6 was 6.13±1.33 (n=56) and 2.79±1.39 (n=66); mean change from baseline was –3.45±1.48 (n=46). Patients in low disease activity (DAS28 <3.2) or remission (DAS28 <2.6) in those who still using TCZ at month 6 was 63.6% and 51.5%. The mean change from baseline in SDAI and CDAI was −28.03±16.75 (n=41) and −24.25±16.94 (n=51), respectively. Of 396 patients, 90 (22.7%) and 8 (2.0%) experienced at least one treatment-emergent AE and SAE, respectively. One patient died of severe pneumonia. Conclusions: This was the first real-world study in RA patients treated with TCZ in China. The results show that Chinese RA patients have long disease history. TCZ was frequently used in combination with DMARDs, especially with ≥2 types of DMARDs. Compared with the dose recommendations, shorter treatment duration and longer dose interval of TCZ were found in China. TCZ demonstrated effectiveness in treatment of Chinese RA patients in real-life clinical practice with manageable safety profile. Acknowledgements: This study was sponsored by Shanghai Roche Pharmaceuticals Limited. Disclosure of Interest: None declared